IMPROVEMENT OF SEED GERMINATION BEHAVIOUR IN PHYLLANTHUS AMARUS BY ACID AND MECHANICAL SCARIFICATION PRETREATMENTS - Gehlot, Meenu; Kasera, Pawan K. (Ecoprint: An International Journal of Ecology, 2014)
Phyllanthus amarus (Bhui-Aanwalaa: Family: Euphorbiaceae) is considered to be the most important medicinal plant of the Indian Thar desert. The present article deals with its seed morphological parameters, seed output, reproductive capacity (RC), germination behavior, seedling growth, root: shoot ratio (R/S ratio), germination value (GV) and vigour index (VI) in fresh and one-year-old seeds under controlled laboratory conditions. Results revealed that 73.33 and 60% germination was observed in fresh and one-year-old seeds as compared to the control (20% in fresh; while 36.67% in one-year-old seeds) after providing mechanical + conc. H2SO4 scarification for 2 and 1 min, respectively. The maximum VI and GV were obtained in mechanical + conc. H2SO4 scarification for 2 min pretreatments in fresh seeds. DOI: http://dx.doi.org/10.3126/eco.v19i0.9848 Ecoprint An International Journal of Ecology Vol. 19, 2012 Page: 1-5 Uploaded date: 2/14/2014